WAWASAN AL-QUR’AN TENTANG IBADAH - Said, Suarning (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract: This paper will try to discuss some verses related to the matter of worship. The command of worship in the Qur'an has two forms, namely by using the word worship with the form fi'il amr and sometimes also use the word nusuk, both of which have the meaning of demands to carry out a command. Implementing the worship ceremony is a necessity for every creature, for as a weak creature, who at all times needs protection, mercy and compassion from the Creator then to obtain all that must be through obedience and steadfast exercise (worship).